2015
DOI: 10.2105/ajph.2015.302903
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Racial/Ethnic Bias Among Health Care Professionals and Its Influence on Health Care Outcomes: A Systematic Review

Abstract: Most health care providers appear to have implicit bias in terms of positive attitudes toward Whites and negative attitudes toward people of color. Future studies need to employ more rigorous methods to examine the relationships between implicit bias and health care outcomes. Interventions targeting implicit attitudes among health care professionals are needed because implicit bias may contribute to health disparities for people of color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
1,150
7
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,654 publications
(1,289 citation statements)
references
References 63 publications
26
1,150
7
13
Order By: Relevance
“…The roles of racism 13,14 and bias 43 in health care inequalities also deserves further investigation. The Institute of Medicine found that “bias, stereotyping, prejudice, and clinical uncertainty on the part of healthcare providers may contribute to racial and ethnic disparities in healthcare.” 44 Sigurdson et al 45 summarized provider and family experiences with unequal NICU care and characterized them as neglectful, judgmental, or systems based, targeting families rather than infants.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of racism 13,14 and bias 43 in health care inequalities also deserves further investigation. The Institute of Medicine found that “bias, stereotyping, prejudice, and clinical uncertainty on the part of healthcare providers may contribute to racial and ethnic disparities in healthcare.” 44 Sigurdson et al 45 summarized provider and family experiences with unequal NICU care and characterized them as neglectful, judgmental, or systems based, targeting families rather than infants.…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions are reinforced when providers use dominant communication and display an attitude that is not collaborative, warm, friendly, and respectful when interacting with AA patients. 29 In addition to preconceptions about Caucasian providers, AAs also rely on previous experiences as reasons for their mistrust of providers. Because AAs have higher rates of public insurance and not being insured, they may expect financial discrimination in the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in interactions with the healthcare system, African Americans report lower quality of care and may suffer from implicit racial bias of their providers. 32 In general and within the cohort, African Americans are more often of low SES (Appendix Table 2), which is known to adversely affect mortality outcomes, 33 even after adjustment for individual lifestyle behaviors. 34,35 Additionally, in comparison with white Americans, on average, African Americans have less wealth, defined as total monetary assets minus debts.…”
Section: Discussionmentioning
confidence: 99%